The impact of genetic polymorphisms in candidate genes on susceptibility to epilepsy and responsiveness to antiepileptics in patients with epilepsy / Hidayati Mohd Sha'ari - Hidayati, Mohd Sha'ari (2016)
Epilepsy is a common neurological disorder with a prevalence of 1%, characterized by more than two seizures (de Boer et al., 2013). Medically intractable to antiepileptic drug (AED) treatment for epilepsy has led to the needs of pharmacogenomics study of AEDresistant in epilepsy patients. The aim of this study was to investigate the association of 17 candidate single nucleotide polymorphisms (SNPs) with susceptibility to epilepsy or drug responsiveness in 1152 epilepsy patients and 1532 healthy controls. Out of 1152 patients, 579 were drug responders while the remaining were drug non-responders, receiving AED for at least one year. Adjusted results by covariates showed significant associations between BDNF rs6265, rs7103411 and rs7127507 (OR 2.1, 95% CI 1.5-3.0, p = 0.0001; OR 0.5, 95% CI 0.4-0.7, p = 0.0003; and OR 0.6, 95% CI 0.4-0.8, p = 0.002, respectively), CALHM1 rs11191692 (OR 0.6, 95% CI 0.4-0.8, p = 0.002), ASIC1 rs844347 (OR 1.7, 95% CI 1.2-2.4, p = 0.002), and GRIK2 rs4840200 (OR 1.6, 95% CI 1.2-2.2, p = 0.001) with susceptibility to epilepsy. The ABCC2 rs2273697 and the KCNAB1 rs2280032 showed significant association with AED responsiveness (OR 6.0, 95% CI 2.1-17.2, p = 0.001 and OR 0.4, 95% CI 0.3-0.7, p = 0.001, respectively). In conclusion, this study suggests that the BDNF rs6265, rs7103411 and rs7127507, CALHM1 rs11191692, ASIC1 rs844347 and GRIK2 rs4840200 might be risk variants for susceptibility to epilepsy as well as the ABCC2 rs2273697 and KCNAB1 rs2280032 for drug responsiveness. Further studies with larger sample size are needed to prove these findings.